The Impact of Digital Influencers on Attitude Towards Brand, Purchase Intention, and Brand Attachment (The Lumbini Journal of Business and Economics, 2022)
The purpose of this research is to discover if there are any links between digital influencers and three main marketing concepts: attitude towards brand, brand attachment, and purchase intention. The research focused on relationship between the perception of digital influencers and their impact on attitude towards brand, brand attachment, and purchase intention. The result showed significant relationship between credibility and attitude towards brand. Also showed significant relation between familiarity and attitude towards brand but showed insignificant between similarity and attitude towards brand. Likewise, it showed significant relationship between similarity and brand attachment. Also showed significant between familiarity and brand attachment but showed insignificant between credibility and brand attachment. And lastly it showed significant between purchase intention and familiarity. Correspondingly, it showed insignificant between credibility and purchase intention, also showed insignificant between similarity and purchase intention.